Nursing diagnoses, related factors and risk factors during the postoperative period following bariatric surgery - Moreira, Rosa Aparecida Nogueira; Caetano, Joselany Áfio; Barros, Lívia Moreira; Galvão, Marli Teresinha Gimeniz (Revista da Escola de Enfermagem da USP, 2013)
The objective was to identify the main diagnoses, related factors and risk factors regarding the cardiovascular/pulmonary responses class proposed by NANDA version 2009-2011. This case series descriptive study was performed with twenty patients who underwent bariatric surgery in a public hospital in Fortaleza-CE, Brazil. Data were collected by two intensive care unit nurse specialists through interviews, physical examinations and the reviewing of medical records, and analyzed through descriptive statistics and cross-mapping. The nursing diagnoses identified with a frequency greater than 50% were: decreased cardiac output (75%), ineffective breathing patterns (65%), dysfunctional ventilatory weaning response (55%) and ineffective peripheral tissue perfusion (75%); in addition, fourteen related factors and five risk factors were identified. We verified the need for further studies to better define the diagnostic profile of these patients in order to direct nursing care towards the early detection of complications.